Population connectivity and the effectiveness of marine protected areas to protect vulnerable, exploited and endemic coral reef fishes at an endemic hotspot - van der Meer, M.; Berumen, M.; Hobbs, Jean-Paul; van Herwerden, L. (Springer Verlag, 2015)
Marine protected areas (MPAs) aim to mitigate anthropogenic impacts by conserving biodiversity and preventing overfishing. The effectiveness of MPAs depends on population connectivity patterns between protected and non-protected areas. Remote islands are endemism hotspots for coral reef fishes and provide rare examples of coral reefs with limited fishing pressure. This study explored population genetic connectivity across a network of protected and non-protected areas for the endemic wrasse, Coris bulbifrons, which is listed as “vulnerable” by the IUCN due to its small, decreasing geographic range and declining abundance. Mitochondrial DNA (mtDNA) and microsatellite DNA (msatDNA) markers were used to estimate historic and contemporary gene flow to determine the level of population self-replenishment and to measure genetic and genotypic diversity among all four locations in the species range (south-west Pacific Ocean)—Middleton Reef (MR), Elizabeth Reef (ER), Lord Howe Island (LHI) and Norfolk Island (NI). MPAs exist at MR and LHI and are limited or non-existent at ER and NI, respectively.There was no obvious differentiation in mtDNA among locations, however, msatDNA revealed differentiation between the most peripheral (NI) and all remaining locations (MR, ER and LHI). Despite high mtDNA connectivity (M = 259–1,144), msatDNA connectivity was limited (M = 3–9) with high self-replenishment (68–93 %) at all locations. NI is the least connected and heavily reliant on self-replenishment, and the absence of MPAs at NI needs to be rectified to ensure the persistence of endemic species at this location. Other endemic fishes exhibit similar patterns of high self-replenishment across the four locations, indicating that a single spatial management approach consisting of a MPA network protecting part of each location could provide reasonable protection for these species. Thus, the existing network of MPAs at this endemic hotspot appears adequate at some locations, but not at all.